Improving the Motor Skills of Children with Developmental Coordination Disorder - Orifjon Saidmamatov; Raximov Quvondiq Ozodovich (Journal La Edusci, 2021)
Past examinations uncover that the prescient control of developments is weakened in children with Developmental Coordination Disorder (DCD), most likely connected with shortfall within the inner modelling of movements. The aim of the present study was to investigate the effect of a motor skills training program in children with Developmental Coordination Disorder. The study was done at four kindergartens in the Khorezm region of Uzbekistan for duration of 10 weeks. All 27 children with DCD who taken part were referred to the research and score at and below the 16th percentile for their age on the Movement Assessment Battery for Children (MABC 2). Participants were divided into an intervention group (n=18) receiving 10 weeks of motor skills training program for 40 min twice per week and the control group (n=9) proceeded with exercises of everyday living. Twenty-four children finalized the research, with 14 boys and 10 girls (mean age 5.17, SD= 0.702). All children in the intervention group had a sharp increase in total percentile ranking of MABC 2 but a further decrease was observed in the control group except for one child. The study supports 10 weeks of a motor skills training program which can be a beneficial intervention for physical education specialists to enhance motor skills for children with DCD.